Concurrent Trajectories of Objectively Measured Insufficient Recovery and Workload Among a Cohort of Shift Working Hospital Employees: Quantitative Empirical Research - Annina Ropponen; Maria Hirvonen; Tero Kuusi; Mikko Härmä (Wiley, 2024)
ABSTRACT Aim To investigate concurrent changes in short shift intervals (< 11 h) and workload among hospital employees. Design and Data Sources This cohort study of 1904 employees in one hospital district in Finland utilised data on employees' working hours for short shift intervals and workload based on the patient classifications aggregated to a 3‐week period level across 2 years, 2018-2019. The data was analysed by group‐based trajectory modelling and multinominal regression models. Results The seven trajectories model had the best fit to the data-Group 1: very few short shift intervals that are decreasing and low workload (15.0%); Group 2: a low amount of short shift intervals that are decreasing and stable low workload (14.2%); Group 3: moderate amount of short shift intervals that are slightly increasing and low workload (25.1%); Group 4: a low amount of short shift intervals that are slightly decreasing and stable low workload that is slightly increasing (12.1%): Group 5: a moderate amount of both short shift intervals and workload (19.8%): Group 6: short shift intervals that are clearly decreasing, with higher than the average workload decreasing (5.6%); Group 7: moderate amount of short shift intervals and very high workload (8.3%). Conclusions Only a minority of hospital employees were found to have both high workloads and insufficient recovery possibilities, but the time‐related increases in objective workload were not compensated by better recovery possibilities in working hours. For shift scheduling, it is noteworthy that older employees might seek to work at units in which the workload is lower, which could be considered to support workability. Reporting Method Record. Patient or Public Contribution No Patient or Public Contribution.